A user experience perspective on heritage tourism in the metaverse: Empirical evidence and design dilemmas for VR - Baker, Jeffrey (2023)
The tourism industry will be shaped by the growth and development of the metaverse in the coming decades. Virtual reality (VR) will enable the creation of virtual worlds, avatars, digital twins, and new social networks. These technologies can be utilized in tourism to enable travelers to preview real-world experiences, to enhance experiences while on-site, to relive experiences after travel, or in some cases to even substitute for travel. Given the metaverse’s transformative potential, empirical investigation of VR is clearly warranted. Studies of VR tourism typically choose a single specific VR application and investigate its impact on adoption or user satisfaction. This application-level focus is a significant limitation. We therefore evaluate multiple heritage tourism applications as well as VR hardware in a comprehensive and structured analysis from the user experience (UX) perspective. Our content analysis of user interviews reveals 13 factors that shape users’ overall perceptions about VR. These factors are grouped into categories related to presentation of the VR content, the content itself, and the functionality of the hardware and software. Our analysis also reveals three design dilemmas for creators of VR heritage tourism content for the metaverse. Implications and an agenda for future research are included.